2012
DOI: 10.1111/cmi.12062
|View full text |Cite
|
Sign up to set email alerts
|

Early gametocytes of the malaria parasitePlasmodium falciparumspecifically remodel the adhesive properties of infected erythrocyte surface

Abstract: SummaryIn Plasmodium falciparum infections the parasite transmission stages, the gametocytes, mature in 10 days sequestered in internal organs. Recent studies suggest that cell mechanical properties rather than adhesive interactions play a role in sequestration during gametocyte maturation. It remains instead obscure how sequestration is established, and how the earliest sexual stages, morphologically similar to asexual trophozoites, modify the infected erythrocytes and their cytoadhesive properties at the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 45 publications
15
79
0
Order By: Relevance
“…The very low transcript levels of immature gametocytes in the peripheral blood of 20% of the children suggest that the highly sensitive qPCR might be detecting residual early sexual stages in the bloodstream that may have escaped from the bone marrow. These results are in agreement with recent findings suggesting that mechanical properties of erythrocytes infected by immature gametocyte stages (ie, decreased deformability leading to the retention of immature gametocytes within the marrow) [37][38][39] may play a role in their localization in the bone marrow. However, it cannot be ruled out that cytoadhesion of erythrocytes infected by sexually committed trophozoites to specific receptors in the bone marrow may contribute to the enrichment of early sexual stages in this organ.…”
Section: Discussionsupporting
confidence: 93%
“…The very low transcript levels of immature gametocytes in the peripheral blood of 20% of the children suggest that the highly sensitive qPCR might be detecting residual early sexual stages in the bloodstream that may have escaped from the bone marrow. These results are in agreement with recent findings suggesting that mechanical properties of erythrocytes infected by immature gametocyte stages (ie, decreased deformability leading to the retention of immature gametocytes within the marrow) [37][38][39] may play a role in their localization in the bone marrow. However, it cannot be ruled out that cytoadhesion of erythrocytes infected by sexually committed trophozoites to specific receptors in the bone marrow may contribute to the enrichment of early sexual stages in this organ.…”
Section: Discussionsupporting
confidence: 93%
“…1C) (Nilsson et al 2015;Pelle et al 2015). In contrast to asexual stages, early gametocytes do not significantly modify the RBC, as minimal levels of PfEMP-1 are expressed on the infected RBC surface and no significant knob structures were observed Tiburcio et al 2013). This difference in surface protein expression is consistent with in vitro studies in which immature gametocytes showed significantly less, if any, binding to purified host ligands (CD36, ICAM-1) (Day et al 1998) and to bone marrow endothelium or other endothelial cell lines .…”
Section: Sequestration Of Transmission Stagessupporting
confidence: 79%
“…10,11,45,46 The rise in the knob density in mature asexual stages results in the increased number of vertical constraints between the spectrin network and the lipid bilayer, which further stiffens the membrane. 47 In GIEs, KAHRP and PfEMP1 are not expressed 48,49 and STEVORs may perform an analogous role by increasing vertical constraints between the cytoskeleton and the lipid bilayer. Protein-protein interactions essential for the erythrocyte membrane mechanical properties are modulated by posttranscriptional modifications of either cytoskeleton or parasite proteins.…”
Section: Discussionmentioning
confidence: 99%